Asas Horizontal Pada Akta Perjanjian Sewa Menyewa Yang Tanah Sewanya Di Bebani Hak Tanggungan - Jayani, Komang Kory; Mahendrayana, I Made Dwi Dimas; Sumardika, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/AC.2024.v09.i02.p11, 2024)
The purpose of this study is to examine the horizontal principle in land lease agreements burdened with mortgage rights. This study uses a normative method with a statutory and conceptual approach. The results show that the lease of freehold land has the nature of droit de suit, meaning that the lease right continues to follow the land, whoever the owner is. The lease right of buildings on freehold land is closely related to the principle of legal relations between people and land, one of which is the horizontal principle, which states that buildings and plants on the land are not one unit. In the context of mortgage rights as the object of the lease agreement, the tenant's rights must continue to be respected and the lease agreement remains valid until the lease term ends, unless otherwise specified in the agreement. The imposition of mortgage rights on leased land creates a complexity of legal interests between the landowner, tenant, and mortgage holder. The horizontal principle separates the land ownership from the buildings on it, ensuring that the lease right remains valid even if the land ownership changes. This emphasizes the importance of a clear agreement to protect the rights of all parties and clarify the conditions for termination or extension of the lease. This study also highlights the need for legal reform to strengthen the protection of tenant rights when leased land is burdened with mortgage rights.